Work and Identity in an Era of Precarious Employment: How Workers Respond to "Personal Branding" Discourse. Issue 1 (February 2018) - Vallas, Steven P.; Christin, Angèle
Recent efforts to understand the significance of precarious work have been limited in at least two important respects. One is the neglect of the ideological constructs that workers are led to embrace concerning the employment relation, and the other is the undertheorized nature of much research in this field. To address these limits, the authors adopt a two-pronged strategy in this article. In empirical terms, the authors focus on an important source of popular thinking about work: the career advice genre, which has recently evolved into a growing literature on "personal branding." In theoretical terms, the authors appeal to Foucault's theory of governmentality in order to understand how and why workers respond to personal branding discourses. Data are drawn from two linked qualitative studies bearing on workers employed in distinct settings: freelance journalists in Paris and New York ( N  = 101) and a broader set of white-collar employees who have faced market adversity in Boston ( N  = 62). Findings reveal that personal branding discourse has become both prevalent and potent, encouraging many workers to conform to what Foucault referred to as the "enterprising self." Yet the authors also find that workers respond to personal branding in a multiplicity of ways, some of which Foucault left unaddressed. The article thus finds qualified support for Foucault's arguments but identifies issues—especially that of agency and resistance—which stand in need of additional elaboration.